A question of top talent? The effects of lateral hiring in two emerging economies. Issue 11 (17th June 2017) - Amankwah-Amoah, Joseph; Nyuur, Richard B.; Ifere, Simeon
Abstract: On the basis of a qualitative study in two emerging economies, we advance the literature on lateral hiring by developing an integrated phase model to explain how the effects of lateral hiring unfold to affect the originating firm and its employees. Our work uncovered two types of effects on the originating firm, i.e. first-order and second-order effects. Our stage model elucidates how the psychological and emotional effects are manifest to affect the existing employees. Personnel poaching appear to have triggered the quest for meaning and attempts by the existing employees to enhance their visibility, career adaptability and marketability. We discuss implications for practice, theory and research on lateral hiring.